Reflexive methodology new vistas for qualitative research - Alvesson, Mats 1956-; Sköldberg, Kaj 1942- (SAGE, 2018)
"In their overview of the problems of reflexivity and interpretation, Mats Alvesson and Kaj Sk[um]oldberg have provided an invaluable guide to this central aspect of research methodology. The authors review the major intellectual streams; discuss the development of a reflexive methodology; and show how culture, language, selective perception, and ideology all, in complicated ways, permeate scientific activity. They make explicit the links between techniques used in empirical research and different research traditions, making possible a theoretically informed approach to qualitative research."